VII. INFANT SLEEP DEVELOPMENT FROM 3 TO 6 MONTHS POSTPARTUM: LINKS WITH MATERNAL SLEEP AND PATERNAL INVOLVEMENT. Issue 1 (March 2015) - Tikotzky, Liat; Sadeh, Avi; Volkovich, Ella; Manber, Rachel; Meiri, Gal; Shahar, Golan
ABSTRACT: The aims of this longitudinal study were to examine (a) development of infant sleep and maternal sleep from 3 to 6 months postpartum; (b) concomitant and prospective links between maternal sleep and infant sleep; and (c) triadic links between paternal involvement in infant caregiving and maternal and infant sleep. The study included 57 families that were recruited during pregnancy. Maternal and infant sleep was assessed using actigraphy and sleep diaries for 5 nights. Both fathers and mothers completed a questionnaire assessing the involvement of fathers relative to mothers in infant caregiving. The results demonstrated moderate improvement in infant and maternal sleep percent between 3 and 6 months. Maternal sleep percent at 3 months significantly predicted infant sleep percent at 6 months. Greater paternal involvement in infant daytime and nighttime caregiving at 3 months significantly predicted more consolidated maternal and infant sleep at 6 months. These findings suggest that maternal sleep is an important predictor of infant sleep and that increased involvement of fathers in infant caregiving responsibilities may contribute to improvements in both maternal and infant sleep during the first 6 months postpartum.